Inhibition of soluble epoxide hydrolase by cis-4-[4-(3-adamantan-1-ylureido)cyclohexyl-oxy]benzoic acid exhibits antihypertensive and cardioprotective actions in transgenic rats with angiotensin II-dependent hypertension - Neckář, Jan; Kopkan, Libor; Husková, Zuzana; Kolář, František; Papoušek, František; Kramer, Herbert J; Hwang, Sung Hee; Hammock, Bruce D; Imig, John D; Malý, Jiří; Netuka, Ivan; Ošťádal, Bohuslav; et al. (Clinical science (London, England, 2012)
The present study was undertaken to evaluate the effects of chronic treatment with c-AUCB {cis-4-[4-(3-adamantan-1-ylureido)cyclohexyl-oxy]benzoic acid}, a novel inhibitor of sEH (soluble epoxide hydrolase), which is responsible for the conversion of biologically active EETs (epoxyeicosatrienoic acids) into biologically inactive DHETEs (dihydroxyeicosatrienoic acids), on BP (blood pressure) and myocardial infarct size in male heterozygous TGR (Ren-2 renin transgenic rats) with established hypertension. Normotensive HanSD (Hannover Sprague-Dawley) rats served as controls. Myocardial ischaemia was induced by coronary artery occlusion. Systolic BP was measured in conscious animals by tail plethysmography. c-AUCB was administrated in drinking water. Renal and myocardial concentrations of EETs and DHETEs served as markers of internal production of epoxygenase metabolites. Chronic treatment with c-AUCB, which resulted in significant increases in the availability of biologically active epoxygenase metabolites in TGR (assessed as the ratio of EETs to DHETEs), was accompanied by a significant reduction in BP and a significantly reduced infarct size in TGR as compared with untreated TGR. The cardioprotective action of c-AUCB treatment was completely prevented by acute administration of a selective EETs antagonist [14,15-epoxyeicosa-5(Z)-enoic acid], supporting the notion that the improved cardiac ischaemic tolerance conferred by sEH inhibition is mediated by EETs actions at the cellular level. These findings indicate that chronic inhibition of sEH exhibits antihypertensive and cardioprotective actions in this transgenic model of angiotensin II-dependent hypertension.
Keywords: Animals; epoxid hydrolasy; hypertenze; Female; kardiotonika; angiotensin II; močovina; ženské pohlaví; Urea; Eicosanoids; Arrhythmias, Cardiac; krevní tlak; Rats, Sprague-Dawley; Epoxide Hydrolases; Hypertension; Male; potkani Sprague-Dawley; benzoáty; Benzoates; Rats, Transgenic; srdeční arytmie; Myocardial Infarction; krysa rodu Rattus; Cardiotonic Agents; Antihypertensive Agents; zvířata; mužské pohlaví; antihypertenziva; Blood Pressure; ikosanoidy; Rats; potkani transgenní; Angiotensin II; infarkt myokardu